Genome-Wide and Trait-Specific Markers: A Perspective in Designing Conservation Programs - Sun, Hao; Olasege, Babatunde Shittu; Xu, Zhong; Zhao, Qingbo; Ma, Peipei; Wang, Qishan; Lu, Shaoxiong; Pan, Yuchun (Frontiers in Genetics, 2018)
Nowadays, breed conservation has entered the genomics era and it is imperative to develop novel theory to design the breeding schemes of the conservation populations by using the genomic information. The genome-wide markers have been regarded as a useful strategy to maintain genetic diversity. However, using the genome-wide SNPs to optimize diversity might not be optimal for some specific loci associated with specific-traits. Using the sequencing data of the conserved population of the Saba pig breed, we demonstrated that the conservation program designed by using the genome-wide SNPs might result in the loss of the genetic diversity of the reproduction trait. We suggested an idea of using phylogenetic tree to select valuable individuals for conservation program based on the genome-wide and trait-specific makers. The selection rule was to make the selected samples to be widely distributed as much as possible in both the genome-wide and trait-specific phylogenetic trees.